MESSAGE SCHEDULING ON CAN BUS FOR SHIP ENGINE SYSTEMS - Favian Dewanta; Dong-Sung Kim; Rendy Munadi (TEKTRIKA, 2016)
This paper reports novel algorithm for handling real time message scheduling on CAN bus which consider buffer occupancy and message type (alarm, periodic real time and non real time). This algorithm is derived to reduce burden of the distributed control unit (DCU) which have obligation to deliver message within strict time and also manage buffer storage occupancy. The algorithm works by changing the message priority which is attached in the identifier field of message frame. The priority adjustment is performed by online calculation prior to send the message on the CAN bus. Finally, this proposed algorithm is applied on ship engine systems which consist of certain number of DCUs. In this networked control system, the proposed algorithm can decrease buffer overflow. Furthermore, the important message alarm and periodic real time message can be delivered within the deadline.Keywords: CAN Bus, message scheduling, DCU